2014
DOI: 10.3851/imp2920
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability and Pharmacokinetics of Doravirine, a Novel HIV Non-Nucleoside Reverse Transcriptase Inhibitor, after Single and Multiple doses in Healthy Subjects

Abstract: Doravirine is generally well tolerated in single doses up to 1,200 mg and multiple doses up to 750 mg once daily for up to 10 days, with a pharmacokinetic profile supportive of once-daily dosing. Doravirine at steady state slightly reduced the exposure of coadministered midazolam, to a clinically unimportant extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
91
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 4 publications
8
91
0
Order By: Relevance
“…Consistent with in vitro and clinical drug-drug interaction findings to date (1,(5)(6)(7), data from the current investigation support the hypothesis that doravirine does not have a clinically meaningful effect on CYP3A4 metabolism or OATP1B1, MDR1, and BCRP transporters, which are implicated in the disposition of atorvastatin (13,14). This observation was justified by the lack of changes in exposure, clearance, and half-life associated with atorvastatin when it was administered both alone and concomitantly with doravirine.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Consistent with in vitro and clinical drug-drug interaction findings to date (1,(5)(6)(7), data from the current investigation support the hypothesis that doravirine does not have a clinically meaningful effect on CYP3A4 metabolism or OATP1B1, MDR1, and BCRP transporters, which are implicated in the disposition of atorvastatin (13,14). This observation was justified by the lack of changes in exposure, clearance, and half-life associated with atorvastatin when it was administered both alone and concomitantly with doravirine.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, doravirine does not inhibit or induce CYP enzymes, including CYP3A4, or inhibit major drug transporters in vitro, suggesting that it has a low potential to cause clinically meaningful drug-drug interactions (5). Consistent with in vitro data, clinical studies have demonstrated that doravirine does not perpetrate clinically meaningful drug interactions with substrates for CYP3A4, breast cancer resistance protein (BCRP), organic cation transporter member 2 (OCT2), organic anion transporter 1 (OAT1), and OAT3 (1,6,7; data on file).…”
supporting
confidence: 51%
See 2 more Smart Citations
“…13 Doravirine is a novel nonnucleoside reverse transcriptase inhibitor designed to overcome the limitations of other drugs within the same class. 22,23 The rapid absorption of doravirine has been shown to result in a median time to maximum concentration (t max ) of 1 to 4 hours and a half-life of 12 to 19 hours for single oral doses of 6 to 1200 mg, 23 and a geometric mean maximum plasma concentration (C max ) of 2.26 μM was achieved at steady state following once-daily dosing. [14][15][16][17] In the United States, doravirine is indicated for administration once daily at a dose of 100 mg, in combination with other antiretroviral agents, for the treatment of HIV-1 infection.…”
mentioning
confidence: 99%